Pengaruh Pelaksanaan Posyandu Lansia terhadap Produktivitas Lansia - Guntur, Muhamad; Muh. Jumaidi Sapwal; Nagib, Muh. (ProHealth Journal, 2024)
The elderly are an important age group for the survival of a country because they are experiencedhuman resources and have very valuable knowledge. Tofind out the Effect of the Implementation of Posyandu for the Elderly on the Productivity of the Elderly in Batu Putik village, Keruak HealthCenter Working Area. This study is an analytical study using a cross sectional design, a sample of66 elderly people in Batu Putik village, Keruak Health Center working area, which was obtainedusing proportionate random sampling. The research instrument used is a questionnaire. Data processing used theSpearman Rho statistical test (p≤ 0.05). In the characteristics of the respondents, the respondents with the highest number of respondents were in the age range of 60-69 years with a total of 45 people (68%), the respondents with the most gender were women witha total of 36 people (55%), the respondents with the highest level of employment were PEtani witha total of 40 people (61%) and the respondents with the highest level of education, namely not in school with a total of 40 people (61%). In the implementation of the posyandu, most of the respondents had a good category of 50 respondents (76%), in the productivity of the elderly, mostof the respondents had a good category of 21 respondents (42.0%). The results of this study concluded that Ha was accepted and Ho was rejected. There is an effect of the implementation ofthe elderly Posyandu on the productivity of the elderly in Batu Putik village, the working area of the Keruak Health Center